Crystallization and preliminary X‐ray crystallographic analysis of human peptidylarginine deiminase type I. Issue 12 (1st December 2013) - Unno, Masaki; Kinjo, Saya; Kizawa, Kenji; Takahara, Hidenari
<x xml:space="preserve">Abstract</x> Peptidylarginine deiminase (PAD) catalyzes the post‐translational conversion of peptidylarginine to peptidylcitrulline in the presence of calcium ions. Among the five known human PAD isozymes (PAD1–4 and PAD6), PAD1 exhibits the broadest substrate specificity. Crystals of PAD1 obtained using polyethylene glycol 3350 as a precipitant diffracted to 3.70 Å resolution using synchrotron radiation. Two PAD1 molecules were contained in the asymmetric unit and the crystals belonged to space group P61, with unit‐cell parameters a = b = 90.3, c = 372.3 Å. The solvent content was 58.2%.